1994
DOI: 10.1126/science.266.5190.1540
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Control of the SrTiO 3 Crystal Surface

Abstract: The atomically smooth SrTiO(3) (100) with steps one unit cell in height was obtained by treating the crystal surface with a pH-controlled NH(4)F-HF solution. The homoepitaxy of SrTiO(3) film on the crystal surface proceeds in a perfect layer-by-layer mode as verified by reflection high-energy electron diffraction and atomic force microscopy. Ion scattering spectroscopy revealed that the TiO(2) atomic plane terminated the as-treated clean surface and that the terminating atomic layer could be tuned to the SrO a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
709
1
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,192 publications
(720 citation statements)
references
References 12 publications
9
709
1
1
Order By: Relevance
“…Recent work has suggested that the SrTiO 3 surface can be selectively altered through pH treatments to etch the more acidic TiO 2 or the more basic SrO, and future syntheses which minimize the SrOterminated surfaces may enhance dye adsorptance values and increase photocurrents and IPCE values. 26 Alternately, the sensitizer used has been optimized for anatase, and use of other sensitizers may lead to improved performance through better interfacial characteristics. Figure 6.…”
Section: Resultsmentioning
confidence: 99%
“…Recent work has suggested that the SrTiO 3 surface can be selectively altered through pH treatments to etch the more acidic TiO 2 or the more basic SrO, and future syntheses which minimize the SrOterminated surfaces may enhance dye adsorptance values and increase photocurrents and IPCE values. 26 Alternately, the sensitizer used has been optimized for anatase, and use of other sensitizers may lead to improved performance through better interfacial characteristics. Figure 6.…”
Section: Resultsmentioning
confidence: 99%
“…In 1994, this problem was identified and solved for SrTiO 3 by Masashi Kawasaki, a materials scientist then at the Tokyo Institute of Technology, now at Tohoku University in Japan, who developed a pre-growth treatment involving various acids that strip the crystal substrate down to the desired atomic layer 10 . With this advance, says Kawasaki, "people could finally grow complex oxides".…”
Section: Just One Small Pushmentioning
confidence: 99%
“…43 to produce atomically flat TiO 2 -terminated surface with one unit-cell-high steps. The (001) LaAlO 3 substrates used in this work were treated following the receipe in ref.…”
Section: Methodsmentioning
confidence: 99%